2023
DOI: 10.3390/cancers15030854
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Effectiveness of Sorafenib versus Lenvatinib Combined with PD-1 Inhibitors in Unresectable Hepatocellular Carcinoma

Abstract: Immune checkpoint inhibitors (ICIs) combined with multitarget tyrosine kinase inhibitors (MTKIs) exert a synergistic effect and are effective in unresectable hepatocellular carcinoma (uHCC). However, precise data regarding the real-world clinical applications of these combination therapies in uHCC are lacking. This study compared the treatment efficacy of sorafenib versus lenvatinib in combination with programmed cell death protein-1 (PD-1) inhibitors in patients with uHCC in a clinical setting. Among 208 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…First, patient eligibility is restricted with only those meeting the current inclusion criteria (limited to cases with a Child–Pugh A score) being considered, primarily because of the occurrence of severe immune-related adverse events resulting from the long half-life and off-target effects of mAbs. , Second, the high cost of treatment is rooted in the complexity of mAb production. , Consequently, recent clinical studies have shown a growing inclination toward the incorporation of more cost-effective small-molecule inhibitors. Thus, the combination of small-molecule TKIs with antiangiogenesis properties, such as apatinib (Apa), regorafenib, or lenvatinib, with mAb targeting of PD-1/PD-L1, has displayed enhanced antitumor efficacy in clinical trials for treating advanced HCC. Certainly, the contrasting physicochemical properties inherent to these two types of drugs produce distinct pharmacokinetic profiles. Consequently, when employed concurrently, this divergence in their pharmacokinetics may result in a notable delay in achieving the desired therapeutic effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…First, patient eligibility is restricted with only those meeting the current inclusion criteria (limited to cases with a Child–Pugh A score) being considered, primarily because of the occurrence of severe immune-related adverse events resulting from the long half-life and off-target effects of mAbs. , Second, the high cost of treatment is rooted in the complexity of mAb production. , Consequently, recent clinical studies have shown a growing inclination toward the incorporation of more cost-effective small-molecule inhibitors. Thus, the combination of small-molecule TKIs with antiangiogenesis properties, such as apatinib (Apa), regorafenib, or lenvatinib, with mAb targeting of PD-1/PD-L1, has displayed enhanced antitumor efficacy in clinical trials for treating advanced HCC. Certainly, the contrasting physicochemical properties inherent to these two types of drugs produce distinct pharmacokinetic profiles. Consequently, when employed concurrently, this divergence in their pharmacokinetics may result in a notable delay in achieving the desired therapeutic effectiveness.…”
Section: Introductionmentioning
confidence: 99%